Conceptual approaches to the formation of organizational and economic mechanism of cluster - Shebeko (K.K. Шебеко), K.K.; Khmel (О.А. Хмель), О.А.; Druk (В.Ю. Друк), V.Yu. (Экономика и банки, 2020)
In the article the experience of the EU countries in the formation of clusters has been considered, and basic models of cluster development and possibilities of their implementation in the Republic of Belarus have been distinguished. The authors have also suggested an organizational and economic mechanism of cluster formation, including cross-border clusters, and they have analyzed the role of universities in the development of cluster structures.